To solve the quadratic equation \(-4x^2 - 11x + 3 = 0\) using the quadratic formula, we start with the standard form of the quadratic equation:
\[ ax^2 + bx + c = 0 \]
where
- \(a = -4\),
- \(b = -11\),
- \(c = 3\).
The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
- Calculate the discriminant (\(b^2 - 4ac\)):
- \(b^2 = (-11)^2 = 121\)
- \(4ac = 4 \cdot (-4) \cdot 3 = -48\)
So,
\[ b^2 - 4ac = 121 - (-48) = 121 + 48 = 169 \]
- Now plug the values into the quadratic formula:
\[ x = \frac{-(-11) \pm \sqrt{169}}{2(-4)} = \frac{11 \pm 13}{-8} \]
-
This gives us two possible solutions:
-
First solution: \[ x = \frac{11 + 13}{-8} = \frac{24}{-8} = -3 \]
-
Second solution: \[ x = \frac{11 - 13}{-8} = \frac{-2}{-8} = \frac{1}{4} \]
-
Thus, the solutions to the equation \(-4x^2 - 11x + 3 = 0\) are:
\[ x = -3, \frac{1}{4} \]
Final Answer:
\(x = -3, \frac{1}{4}\)